The Dialectic of Traditionalism and Digitalization: Barriers to Educational Technology Development at the Salafiyah Islamic Boarding School in Curah Kates, Jember - Ahmad Ubaidil Munfarid; Ahmad Rafi Fitroh; Nur Anim Jauhariyah (ICO EDUSHA, 2025)
The rapid development of digital technology has brought significant changes to educational practices, but its implementation in Salafiyah Islamic boarding schools still faces various dynamics and challenges. This study examines the dialectic between traditionalism and digitalization, focusing on the obstacles to the development of educational technology at the Salafiyah Islamic Boarding School in Curah Kates, Jember. The purpose of this study is to analyze the influence of traditional values, institutional culture, and leadership perspectives on the acceptance and implementation of digital-based educational technology. Furthermore, this study aims to identify structural, cultural, and human resource factors that inhibit technological innovation in the Islamic boarding school education system. This study uses a qualitative approach with a case study design. Data collection was conducted through in-depth interviews, participant observation, and documentation studies involving Islamic boarding school leaders, ustadz (Islamic teachers), and students. Data analysis was conducted using interactive analysis techniques that include data reduction, data presentation, and drawing conclusions. The results show that resistance to digitalization is not solely caused by technological limitations, but also by concerns about preserving religious traditions, moral values, and pedagogical authority. This research provides theoretical and practical contributions to the development of Islamic education by proposing a strategy for harmonizing traditional Islamic boarding school values ​​with contemporary digital innovation.